Application of Confocal Laser Scanning Microscopy in Biology and Medicine - I. A. Volkov; N. V. Frigo; L. F. Znamenskaya; O. R. Katunina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Fluorescence confocal laser scanning microscopy and reflectance confocal laser scanning microscopy are up-to-date highend study methods. Confocal microscopy is used in cell biology and medicine. By using confocal microscopy, it is possible to study bioplasts and localization of protein molecules and other compounds relative to cell or tissue structures, and to monitor dynamic cell processes. Confocal microscopes enable layer-by-layer scanning of test items to create demonstrable 3D models. As compared to usual fluorescent microscopes, confocal microscopes are characterized by a higher contrast ratio and image definition.